2007
DOI: 10.1007/s10815-007-9131-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical zona pellucida thinning with acidified Tyrode’s solution: comparison between partial and circumferential techniques

Abstract: Purpose To compare effectiveness of two different chemical zona thinning techniques. Method We studied 163 patients who had experienced IVF or ICSI failures in two or more cycles. Patients were assigned to one of three groups: zona intact (n=72), partial thinning (n = 59), or circumferential thinning (n =73). Before transfer, the zonae pellucidae of embryos were thinned partially or circumferentially using acidified Tyrode's solution. Results Implantation rates were 8.9% in the intact zona group, 17.6% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…However, further long-term studies looking at potential anomalies after birth are needed to assess the safety of QLAH. Whilst various methods of AH are available, a meta-analysis and several comparative studies have suggested little difference in outcomes due to method (Lan et al, 2009;Lanzendorf et al, 2007;Martins et al, 2011;Yano et al, 2007). Therefore, the current study did not consider it profitable to compare the different AH methods.…”
Section: Discussionmentioning
confidence: 87%
“…However, further long-term studies looking at potential anomalies after birth are needed to assess the safety of QLAH. Whilst various methods of AH are available, a meta-analysis and several comparative studies have suggested little difference in outcomes due to method (Lan et al, 2009;Lanzendorf et al, 2007;Martins et al, 2011;Yano et al, 2007). Therefore, the current study did not consider it profitable to compare the different AH methods.…”
Section: Discussionmentioning
confidence: 87%
“…3), (ii) is expelled by a stream procedure until a trough ranging between 20 and 40 μm in width is created in order to perform the drilling [4,21] (Fig. 4), (iii) is used in a microdroplet containing the embryo to perform a circumferential thinning [16,22,23]; and (iv) is used in a microdroplet to prolong the exposure of embryos to a controlled acidified environment to obtain the zona removal [24,25].…”
Section: Chemical Methods: Protocols and Resultsmentioning
confidence: 99%
“…As previously mentioned, a large retrospective comparative study comparing four different methods including laser, PZD, chemical breaching by acidified Tyrode's solution, and ZP thinning using pronase, showed no significant improvement in either implantation or clinical pregnancy rate when compared to non-hatched control groups [42]. Finally, Yano et al [23] randomized 163 patients that experienced ≥ 2 cycles of IVF or ICSI in three groups: (i) partial zona thinning using acidified Tyrode's solution, (ii) circumferential zona thinning, and (iii) intact zona Fig. 4 Procedure commonly used for embryo chemical breaching: [1] the embryo is held by a holding pipette and approached by an AH needle filled by acidified solution; [2] the solution is released gradually and from a distance to assure no harm occur to embryos; [3] the solution release is stopped immediately once a hole is created demonstrating, in disagreement with the previous study, the superiority of partial zona thinning compared to controls without AH in terms of implantation and clinical pregnancy rates.…”
Section: Fresh Embryo Transfer: Zona Thinningmentioning
confidence: 90%
“…Therefore, our results suggest that the area of zona pellucida thinning or opening can affect the outcome of cryopreserved embryo transfer and that higher pregnancy and implantation rates can be attained as the area of zona pellucida thinning or opening increases up to half. However, Yano et al reported higher clinical pregnancy rate (32.2%) after the transfer of partial zona pellucida thinning embryos using acid solution compared with circumferential zona pellucida thinning embryos (27.4%) [23]. Further study evaluating if more than half of zona pellucida thinning could increase the clinical outcome of cryopreserved embryo transfers compared with half thinning may be needed.…”
Section: Discussionmentioning
confidence: 99%